What future teachers believe about democracy and why it is important. Issue 7 (2nd October 2016) - Zyngier, David
Abstract: This paper analyses pre-service education student perceptions and perspectives related to education for democracy in Australia. Using a critical pedagogical framework datum from an online survey, it presents both quantitative and qualitative responses of contrasting understandings of democracy. It begins by outlining the concepts of thick and thin democracy and why this is important in relation to contemporary debates about the state of civics and citizenship education, and then explains the conceptual framework of critical pedagogy and methodology. The datum analysed is discussed in relation to neoliberalism and indicates that the pre-service teachers in this study view democracy in a narrow or thin way that may impact on their classroom practice where they would be teaching about but not for democracy. A more critical and thicker understanding of democracy is suggested as essential if we desire our students to become active and transformative citizens.